Virtual Hotel Operator (VHO) Affiliated Small Accommodation Business: A Comparison of Perceived Performance - Arreza, Mariae Khrisna Baring (Journal of Community Development Research (Humanities and Social Sciences); Vol 15 No 1 (2022): January - March 2022, 2022)
The Virtual Hotel Operator (VHO) is the latest revolution in the hospitality industry that provides an opportunity for small accommodation businesses to compete with more prominent industry players. The VHO expanded and is well applied and advanced in Asia, including Metro Cebu, Philippines, where different VHO brands have partnered with varying arrays of accommodation establishments. VHO supplies the budget traveler and delivers reasonable accommodation with a good value, which has brought impressive changes in the hospitality industry’s traditional systems. However, there is only limited literature about VHO. Thus, in bridging this gap, this paper was centered on the following objectives: Determine the performance of the accommodation businesses affiliated with VHO; Determine the comparison level of the perceived accommodation performance during the VHO partnership; Distinguish the difference of the results among the different VHO brands in Metro Cebu; Determine the advantages and concerns of small accommodation business operators with VHO affiliation and; Test the significant difference of the perceived comparison level among different VHO brands. This study gathered 40 responses from operators of small accommodation businesses in Metro Cebu. This study employed a descriptive method using questionnaires with designated statements that indicate the comparison level of the perceived accommodation performance during the VHO partnership. The findings proved that all the accommodation businesses’ performance has improved during the VHO partnership; specifically, The Metro Cebu small accommodation businesses performance was much better during the VHO partnership. In uncovering the significant difference among the different VHO brands, a non-parametric Kruskal-Wallis test was used, resulted in p = 0.01; thus, there is a significant difference in the comparison level of the perceived accommodation performance during the VHO partnership among VHO brands. Keywords: Virtual Hotel Operator (VHO), Affiliated Small Accommodation Businesses, Perceived Performance, Hospitality Industry